2004
DOI: 10.1038/sj.ejhg.5201240
|View full text |Cite
|
Sign up to set email alerts
|

Inverted duplications: how many of them are mosaic?

Abstract: The best-known situation indissolubly linked to mosaicism is the uniparental disomy where a trisomic or monosomic zygote develops at least one cell line with 46 chromosomes. The mosaicism normal/abnormal cell lines may remain confined to placenta or persist in the embryo. Here, we describe a second situation that might also be indissolubly linked to a mosaic condition or at least to a confined placental mosaicism. We analysed the case of a mosaicism del(8p)/inv dup(8p) found in prenatal diagnosis. We had alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Indeed, the finding that interphase FISH analysis with the subtelomeric probe (TEL8q Cytocell) (Figure 2a) showed two clearly separated signals suggests that a single copy region might be present distal to the duplicated one. Although we could not demonstrate the presence of the distal deletion associated to the duplication, we cannot exclude it and it seems likely that the original product of the abnormal maternal meiosis originating the rearrangement present in the proposita were a dicentric chromosome 8pter-8q24.3H8p24.3-8pter that, at meiosis II or during early embryogenesis, 26 underwent a breakage leading to the present inv dup(8)(q24.3) characterized by a very distal 8q deletion and a 2.3 Mb duplication.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, the finding that interphase FISH analysis with the subtelomeric probe (TEL8q Cytocell) (Figure 2a) showed two clearly separated signals suggests that a single copy region might be present distal to the duplicated one. Although we could not demonstrate the presence of the distal deletion associated to the duplication, we cannot exclude it and it seems likely that the original product of the abnormal maternal meiosis originating the rearrangement present in the proposita were a dicentric chromosome 8pter-8q24.3H8p24.3-8pter that, at meiosis II or during early embryogenesis, 26 underwent a breakage leading to the present inv dup(8)(q24.3) characterized by a very distal 8q deletion and a 2.3 Mb duplication.…”
Section: Discussionmentioning
confidence: 76%
“…DNA extraction, labeling, hybridization and detection and FISH experiments were undertaken, as described previously. 9 We also performed analysis of the breakpoints with self-chain and segmental duplications repeats tools from UCSC Genome Bioinformatics (http://genome.ucsc.edu/).…”
Section: Methodsmentioning
confidence: 99%
“…The dicentric chromosome, in theory, can undergo breakage during meiosis or it can be inherited as such in the zygote. A few cases of mosaicism with different derivatives of the dicentric indeed suggest that the dicentric is usually present in the zygote: both Soler et al (11) and Pramparo et al (12) found in chorionic villi samples two cell lines, one with a del(8)(p11), the other one with an inv dup del(8p). In the case analyzed by Pramparo et al, a third cell line was also present with an inv dup del(8p) ending with the satellites of a D or a G short arm, suggesting that here the inv dup del(8p) had been stabilized through telomere capture leading to a translocated inv dup del chromosome.…”
Section: History Of a Recurrent Rearrangementmentioning
confidence: 96%